An Analysis of Students’ Needs in Reading Comprehension of Eight Grader of SMP IT Fathona Baturaja - Henny Yulia (Edukasi Lingua Sastra, 2020)
The Problems of the study concerned with whether or not the students’ need English for specific purposes in reading. In addition, the study was done to find out the student’s need in reading comprehension. Total sampling method was used to take the sample. The sample was 11 students from the eighth grade in academic year 2019/2020. A Descriptive method was used in this study. The writer used questionnaires and documentation in collecting the data. The result of study from view of Target needs (necessities) showed that 72.8% claimed that they hope that learning English could support their future works. The result of target needs showed that 45.5% were in beginner level. 81.8% want to be able to master both general vocabulary and Islamic world terms. Moreover, the result of learning needs, input in reading comprehension 72.7% claimed that reading can add English vocabulary. From procedure in reading, 54.5% said that they were agree with arranging random paragraphs or sentences into a correct or logical paragraph sequence of sentence. Next, 90.9% students wanted to do the study outside the classroom, 45.5% claimed that they were strongly agree with activity in discussing and being active in investigation. The last, 54.5% students were strongly agreed that teachers must create an active atmosphere to solve problems and doing assignment.